Methylation of TFAM gene promoter in peripheral white blood cells is associated with insulin resistance in adolescents - Gemma, Carolina (2010)
Purpose: To explore whether DNA methylation of the mitochondrial transcription factor A (TFAM) promoter is associated with insulin resistance in a sample of adolescents with features of metabolic syndrome. Methods: The data and blood samples were collected from 122 adolescents out of a cross-sectional study of 934 high-school students. The population was divided into two groups: noninsulin resistance (NIR) and insulin resistance (IR). After bisulfite treatment of genomic DNA from peripheral leukocytes, we used methylation-specific polymerase chain reaction (PCR) to assess DNA methylation of three putative methylation target sites (CpG) in the TFAM promoter. Results: The ratio of the promoter methylated DNA/unmethylated DNA was 0.012+/-0.0009 (1.2% of alleles), and inversely correlated with the biochemical features of insulin resistance (plasma fasting insulin R: -0.26, p<0.004 and homeostasis model assessment (HOMA) index R: -0.27, p<0.002), and obesity (R: -0.27, p<0.002). Multiple regression analysis showed that the log-transformed HOMA index correlated with the status of promoter methylation of TFAM, independently of body mass index (BMI) Z score (beta: -0.33+/-0.094, p=0.00094). Finally, the TFAM promoter methylated DNA/unmethylated DNA ratio was found to be significantly associated with insulin resistance as dichotomous variable (NIR n=45, 0.014+/-0.002 and IR n=77, 0.011+/-0.001, respectively, p<0.016). Conclusion: Our findings suggest a potential role of promoter TFAM methylation in the pathogenesis of insulin resistance in adolescents.